Pembelajaran Mata Pelajaran Fiqih di Madrasah Ibtidaiyah Semarang - Hadi, Sholikhul; Raharjo, Raharjo (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research aims to explain and describe the implementation of fiqih learning in madrasah ibtidaiyah Semarang which includes subject matter of fiqih learning, fiqih learning process, and result of learning fiqih. The method used is descriptive qualitative analysis, namely describing the data accompained by critical analysis. The result of the research can be concluded in general that the implementation of fiqih learning in Madrasah Ibtidaiyah is carried out by teachers very well and efficiently, this can be proven from several things, namely: 1) Fiqih learning consists of affective, cognitive and psychomotor subject. 2) The fiqih learning process in Madrasah Ibtidaiyah uses a constructivist approach, this makes learning very well and efficient because many indicators show that students can follow the lesson well. 3) The students learning outcomes obtained good result because the learning carried out is contextual learning and problem solving.